2019
DOI: 10.18383/j.tom.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Myositis-Induced Models of Bacterial Infection and Inflammation with T2-Weighted, CEST, and DCE-MRI

Abstract: We used T2 relaxation, chemical exchange saturation transfer (CEST), and dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) to assess whether bacterial infection can be differentiated from inflammation in a myositis-induced mouse model. We measured the T2 relaxation time constants, %CEST at 5 saturation frequencies, and area under the curve (AUC) from DCE-MRI after maltose injection from infected, inflamed, and normal muscle tissue models. We applied principal component analysis (PCA) to reduce d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This represents the relative difference in signal intensity between the two tissues. Previous studies have shown that DCE-CNR values can be used to effectively classify different tissue classes [ 25 ]. Generally, the factors that influence CNR are the inherent differences between tissues and the imaging technology used.…”
Section: Discussionmentioning
confidence: 99%
“…This represents the relative difference in signal intensity between the two tissues. Previous studies have shown that DCE-CNR values can be used to effectively classify different tissue classes [ 25 ]. Generally, the factors that influence CNR are the inherent differences between tissues and the imaging technology used.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, novel modalities, such as MR spectroscopy (MRS), chemical exchange saturation transfer (CEST) contrast, Amide Proton transfer imaging and dynamic contrast-enhanced imaging can detect physiological or metabolic changes without the need of exogenous agents. In animal models, these novel MRI capabilities differentiated bacterial infections from sterile inflammation or oncological processes[ 62 , 63 ].…”
Section: Imaging Methods In Tuberculosismentioning
confidence: 99%
“…40 Novel MRI techniques have also been shown to differentiate sterile inflammation or oncological processes from bacterial infections in animal models. 41,42 Ultrasound has been used to show tuberculosis lymphadenopathy, 43,44 and protocols using the suprasternal window have detected abnormalities more frequently than radiography. 45,46 Although ultrasound is radiation-free and a relatively inexpensive technology, it is operatordependent and thus has variable accuracy.…”
Section: Currently Available Imaging Toolsmentioning
confidence: 99%